Efektivitas Pembelajaran Mendalam dalam Implementasi Kurikulum Merdeka di SD Negeri Cikampek Selatan I - Eryanto, Dwi; Prasetyono, Hendro (Jurnal Evaluasi Pendidikan, 2025)
The Independent Curriculum is an educational innovation providing flexibility for schools to design learning strategies suited to students’ characteristics. This study evaluates the effectiveness of implementing the Independent Curriculum using the Deep Learning approach at SD Negeri Cikampek Selatan I. The research employed a descriptive qualitative method through interviews, observations, and document analysis. Data were analyzed using an interactive model consisting of data reduction, presentation, and conclusion drawing. The findings show that applying deep learning principles enhances student engagement, independence, and critical thinking. Teachers have begun implementing conscious, meaningful, and joyful learning by integrating intellectual, emotional, aesthetic, and physical aspects. However, challenges remain in teacher readiness for new pedagogical practices and limited digital learning facilities. Recommendations emphasize strengthening teacher capacity in deep learning, fostering collaborative learning, and optimizing technology use to support meaningful and sustainable learning. Keywords: Independent Curriculum, Deep Learning, Student Engagement, Teacher Readiness, Meaningful Learning.